Information Technology in Laboratory Lessons of The General Physics Course - Saydayev Obid Bahodir oʻgʻli (Genius Journals, 2024)
The paper describes an approach to organizing laboratory workshops on electromagnetism, which consists in using the “Virtual Laboratory”. By conducting laboratory research, students not only confirm the known laws of physics, but also learn to work with physical instruments and master the skills of practical research. Interactive virtual laboratory and practical work is a learning environment that, using computer interactive visualization, allows schoolchildren to simulate a real experiment and conduct educational research. This is an educational environment aimed at ensuring the development of the student’s skills to independently generate new knowledge, formulate ideas, concepts, hypotheses about objects and phenomena, including previously unknown ones, recognize the deficits of their own knowledge and competencies, and plan their development
Keywords: organization of laboratory workshops; virtual instrument; workshop